2011
DOI: 10.1016/j.rbmo.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Histidine-rich glycoprotein polymorphism and pregnancy outcome: a pilot study

Abstract: Histidine-rich glycoprotein (HRG) is involved in fibrinolysis and coagulation, the immune system and angiogenesis. These processes are all crucial in establishing and maintaining pregnancy. The primary aim of this pilot study was to determine if HRG affects pregnancy outcome. The secondary aim was to investigate if a specific genetic polymorphism (rs9898 C/T) in the HRG gene is associated with pregnancy results. The polymorphism leads to expression of either a serine or proline residue at position 186 in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…We have previously shown that HRG might be of importance in early pregnancy and this is supported by our prior results indicating an association between the presence of HRG in placenta and risk of preeclampsia during pregnancy [15], as well as between the HRG C633T SNP and pregnancy outcome among patients undergoing in vitro fertilization [18]. …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We have previously shown that HRG might be of importance in early pregnancy and this is supported by our prior results indicating an association between the presence of HRG in placenta and risk of preeclampsia during pregnancy [15], as well as between the HRG C633T SNP and pregnancy outcome among patients undergoing in vitro fertilization [18]. …”
Section: Discussionsupporting
confidence: 74%
“…HRG has been reported to exist as at least ten naturally occurring single nucleotide polymorphisms (SNPs) [16,17]. One of the SNPs, the HRG C633T SNP, has been postulated to be of relevance for implantation and a successful pregnancy [18] and there is an increased occurrence of the homozygous T/T genotype in patients with primary recurrent miscarriage [19]. …”
Section: Introductionmentioning
confidence: 99%
“…The protein has a naturally occurring single nucleotide polymorphism (SNP) in the gene denoted HRG C633T, which results in an amino acid change from proline to serine at position 204 in the protein (in some publications this amino acid is denoted with position 186 in the protein, which describes the protein without its signal peptide). An association between the HRG C633T SNP and pregnancy outcome among patients undertaking in vitro fertilization has been suggested, where women with HRG 633T have a lower than expected pregnancy rate . The aim of this study was to examine the possible association between the HRG 633T SNP and RM.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of CPN in AD is not clear. HRG is involved in fibrinolysis and coagulation [51], and also plays a role in inflammation and immunity [52]. The role of HRG in AD has not been fully investigated, and only one study reported that HRG was decreased in AD sera [53].…”
Section: Discussionmentioning
confidence: 99%